Retinoblastoma: An overview of modern management - Dhami, Abhinav; Bansal, Aditya; Khetan, Vikas (Nepalese Journal of Ophthalmology, 2017)
Retinoblastoma (RB) is an embryonic tumor originating from the retinal cells. RB is the most common intraocular cancer of childhood and accounts for 4% of all pediatric malignancies.